Kesehatan Fisik pada Klien Tuberkulosis Paru dan Program Rehabilitasi: Kajian Literatur - Kausar, Lola Illona Elfani; Nursasi, Astuti Yuni (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Pulmonary tuberculosis is a disease with a high prevalence in Indonesia and in the world, and continues toincrease every year. Global prevalence reached 10 million cases in 2017 with 1.3 million deaths, and inIndonesia reached up to 1,017,290 cases. Pulmonary TB is one of the leading causes of death in the world.The cause of pulmonary TB continues to increase is easy transmission and vulnerable individual and socialfactors. Many problems are caused by pulmonary TB, especially the physical health problems of the patientwhich can cause various negative impacts. So, the treatment regimen is not enough in the prevention of thisdisease, but requires other interventions such as pulmonary rehabilitation programs. This study aims todescribe of the physical health of pulmonary TB patients with a literature review method of relevant studies,referenced from articles published and indexed internationally by Scopus for the period 2014-2019 inEnglish and can be accessed full text, with keywords the physical health status of pulmonary TB, pulmonaryTB rehabilitation, and pulmonary tuberculosis. Method of analysis by selecting articles according toinclusion criteria set by researchers, and obtained 11 articles. The analysis describes that in pulmonary TBpatients there are physical health problems that cannot be ignored like weight loss, pain and discomfort,fatigue and physical weakness, lack of energy and a decrease in the ability of daily activities, rest and sleepdisturbances, and a decrease in the mobility.